Comparative evaluation of the efficacy of nicotine chewing gum and nicotine patches as nicotine replacement therapy using salivary cotinine levels as a biochemical validation measure - T Sivasankari; Avudaiappan Sankaran; Senthil Murugappan; Veni Subramanyam; Balanehru Subramanian; RC Jagat Reddy; S Vandana (Indian Journal of Psychiatry)
Background: Nicotine replacement therapy (NRT) and habit cessation counseling are considered the mainstay treatment for high nicotine dependence smokers. However, adherence to NRT is very poor. Among the NRTs, nicotine gums and nicotine patches are the most widely available. This study mainly evaluates the efficacy of nicotine gum and nicotine patches as NRT using salivary cotinine levels as a biochemical validation measure. Materials and Methods: A cross-sectional study was conducted on 72 known smokers who were willing to receive nicotine replacement therapy for cessation of smoking habits. The sample was divided into two groups: Group 1 tobacco smokers were offered nicotine chewing gum, and group 2 tobacco smokers were offered nicotine patches. Both groups received treatment for 12 weeks. At baseline and at the end of the trial period, the saliva samples were analyzed for cotinine levels using an enzyme-linked immunosorbent assay (ELISA). The severity of smoking was assessed using the Fagerstrom Test for Nicotine Dependence (FTND). Results: The quit rate was higher in the nicotine patch group compared with the nicotine gum group. On comparison of week one vs week twelve in the nicotine group nicotine gum group showed (CI: 18.10 to 13.83) and in the patch group (CI: 7.754 to 6.56) with P < 0.001. The pre- and post-cotinine estimation was significantly reduced for nicotine patches compared with nicotine gums, and patient compliance also yielded better results for nicotine patches. Conclusion: This study depicts that nicotine patches were better adhered to in comparison with nicotine gums, and salivary cotinine level is an effective biochemical validation measure.